Expert advice for prescribing cannabis medicines for patients with epilepsy—drawn from the Australian clinical experience. Issue 7 (8th March 2022) - Lawson, John; O'Brien, Terry; Graham, Myfanwy; Renaud, Elianne; Jones, Dean; Freeman, Jeremy; Lawn, Nicholas; Martin, Jennifer H.
Abstract : There is international interest for consensus advice for prescribers working in the field of drug resistant epilepsy intending to trial potential therapies that are nonregistered or off‐label. Cannabinoids are one such therapy. In 2017, the New South Wales State Government (Australia) set up a cannabinoid prescribing guidance service for a wide variety of indications, based on known pharmacology together with the relevant new literature as it became available. Increasing interest in cannabis medicines use outside this State over the following 5 years together with a paucity of registration‐standard clinical trials, lack of information around dosing issues, drug interactions and biological plausibility meant there remained a large unmet need for such advice. To address the unmet need in epilepsy, and until medicines were registered or regulator quality data were available, it was agreed to bring together a working group comprising paediatric and adult epilepsy specialists, clinical pharmacists., clinical pharmacologists and cannabis researchers from across Australia to develop interim consensus advice for prescribers. Although interim, this consensus advice addresses much of the current practice gap by providing an informed overview of the different cannabis medicines currently available for use in the treatment of epilepsy in paediatric and adult settings, with information on dose, drug interactions, toxicity, type of seizure and frequency of symptom relief. As such it supplements the limited evidence currently available from clinical trials with experience from front‐line practice. It is expected that this consensus advice will be updated as new evidence emerges and will provide guidance for a subsequent Guideline.